H-NS Plays a Role in Expression of Acinetobacter baumannii Virulence Features - Eijkelkamp, Bart A. (American Society for Microbiology, 2013)
Acinetobacter baumannii has become a major problem in the clinical setting with the prevalence of infections caused by multidrug-resistant strains on the increase. Nevertheless, only a limited number of molecular mechanisms involved in the success of A. baumannii as a human pathogen have been described. In this study, we examined the virulence features of a hypermotile derivative of A. baumannii strain ATCC 17978, which was found to display enhanced adherence to human pneumocytes and elevated levels of lethality toward Caenorhabditis elegans nematodes. Analysis of cellular lipids revealed modifications to the fatty acid composition, providing a possible explanation for the observed changes in hydrophobicity and subsequent alteration in adherence and motility. Comparison of the genome sequences of the hypermotile variant and parental strain revealed that an insertion sequence had disrupted an hns-like gene in the variant. This gene encodes a homologue of the histone-like nucleoid structuring (H-NS) protein, a known global transcriptional repressor. Transcriptome analysis identified the global effects of this mutation on gene expression, with major changes seen in the autotransporter Ata, a type VI secretion system, and a type I pilus cluster. Interestingly, isolation and analysis of a second independent hypermotile ATCC 17978 variant revealed a mutation to a residue within the DNA binding region of H-NS. Taken together, these mutants indicate that the phenotypic and transcriptomic differences seen are due to loss of regulatory control effected by H-NS.